Ayurvedic Management of Peripheral Vascular Disease (International Journal of Ayurveda and Pharma Research, 2025)
Peripheral Arterial Disease (PAD) is a condition that reduces blood flow to the lower limbs due to arterial narrowing It is commonly caused by atherosclerosis and aggravated by chronic smoking. In Ayurveda, PAD can be correlated with Vatarakta, a condition arising from vitiation of Vata and Rakta leading to obstruction and impaired circulation. The patient had severe pain, burning sensation, numbness, and difficulty in walking. A comprehensive Ayurvedic treatment was administered in four stages, including Udwarthanam, Snehapana, Virechana, Dasamoola Ksheeradhara, Jaloukavacharana (leech therapy), and Shilajit Rasayana. Internal medicines like Guggulutiktakam Kashayam, Kaishora Guggulu, and Chandraprabha Vati were also used. After completion of therapy, the patient showed complete relief from symptoms, restoration of peripheral pulses, and improved blood flow, with Doppler ultrasound revealing conversion of monophasic to biphasic flow in the anterior tibial artery. The treatment helped reduce inflammation, improve circulation, and rejuvenate vascular tissues. This case highlights the potential effectiveness of Ayurvedic therapies in improving both symptoms and hemodynamic parameters in PAD. Although the results are promising, larger clinical studies are needed to further validate the role of Ayurveda in managing peripheral vascular diseases.